Вплив гранулометричного складу пороутворювача на структуру та властивості пористого литого алюмінію - Биба, Є.Г.; Мініцький, А.В.; Коваленко, В.В.; Кивгило, Б.В.; Ямшинський, М.М.; Лук’яненко, І.В. (Physico-technological Institute of Metals and Alloys, 2025)
Porous materials made of aluminum powders are attracting attention due to the non-scarcity of raw materials, high corrosion resistance, and low density compared to similar materials based on copper and stainless steel. However, these materials still have not found wide practical applications because of the presence of a non-recoverable aluminum oxide film on the surface of aluminum powder particles, preventing metal contact formation between the particles. Porous cast aluminum can be the solution to all these problems. Porous cast aluminum has better characteristics, making it a promising analog of the proposed porous permeable materials. The paper analyzes technological parameters of producing porous cast aluminum (PCA) by vacuum impregnation method using NaCl as a foaming agent. It was found that the particle size of the blowing agent directly affects the porosity: larger particles reduce the contact area and are less densely distributed in the material body. The geometric shape of the particles also has an impact on porosity: irregularly shaped particles have a larger contact area and are more densely packed than spherical particles. It was discoveredthat NaCl is completely extracted from the samples, the pores have a variety of geometric shapes, and with an increase in the fraction of the pore-forming agent, the pore size increases. The analysis of microstructures showed that with an increase in the fraction of a forming agent, the average pore size and apertures also increase. The research indicated that the size of a forming agent determines the strength characteristics of the PCA; with an increase in the foaming agent fraction, and the pore size respectively, the strength grows. It was revealed that the permeability coefficient is sensitive to the pressure drop and goes up significantly with an increase in pore size, which is determined by the particle size composition of the filler. In addition, it was established that the higher the porosity, the higher the permeability coefficient. The results of the research showed the prospects of using PCA as filter elements operating under conditions of significant pressure drops and aggressive media.